1985
DOI: 10.1111/j.1469-8137.1985.tb02786.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Responses to Vesicular‐arbuscular Mycorrhiza

Abstract: Light and temperature greatly influenced the development of vesicular-arbuscular mycorrhiza and growth of onions in a phosphate-deficient soil. There were more large arbuscules and host growth was stimulated more with 25,000 lux than with 13,000 lux at 23° C and in a 14-23° C diurnal cycle. At 14° C and 13,000 lux mycorrhiza caused no growth stimulation even in three low-phosphate soils. At 18° C infection was much sparser in a 6 h daylength than in 12 and 18 h. Mycorrhizal plants kept in daylengths of 6 h at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
1
4

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 15 publications
2
80
1
4
Order By: Relevance
“…However, constant (instead of decreasing) hexose or Suc levels in mycorrhizal tobacco and Medicago roots indicate the sufficient availability of carbohydrates in wild-type plants under normal growth conditions. In contrast, according to previous experiments that show a reduced mycorrhization upon limiting light intensity (Hayman, 1974;Tester et al, 1985;Son and Smith, 1988), suppression of AM could be observed if the root was severely undersupplied with carbohydrates as shown for NT rolCTppa plants. During the disturbed inorganic pyrophosphatase-dependent uptake of Suc into the phloem cells and translocation of Suc to the sink tissue (Lerchl et al, 1995), the formation of AM was characterized by less density of fungal storage organs, indicating a deficiency of carbon.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…However, constant (instead of decreasing) hexose or Suc levels in mycorrhizal tobacco and Medicago roots indicate the sufficient availability of carbohydrates in wild-type plants under normal growth conditions. In contrast, according to previous experiments that show a reduced mycorrhization upon limiting light intensity (Hayman, 1974;Tester et al, 1985;Son and Smith, 1988), suppression of AM could be observed if the root was severely undersupplied with carbohydrates as shown for NT rolCTppa plants. During the disturbed inorganic pyrophosphatase-dependent uptake of Suc into the phloem cells and translocation of Suc to the sink tissue (Lerchl et al, 1995), the formation of AM was characterized by less density of fungal storage organs, indicating a deficiency of carbon.…”
Section: Discussioncontrasting
confidence: 45%
“…Moreover, higher carbon availability was shown to stimulate the phosphate allocation (Bü cking and Shachar-Hill, 2005). Conversely, limiting light intensity reduced mycorrhization and lead to decreased growth and phosphate uptake (Hayman, 1974;Tester et al, 1985;Son and Smith, 1988).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outro aspecto relevante é estudar a eficiência dos FMA nativos que além de ser fácil e rápido de se obter esse inóculo puro, seus benefícios têm sido relatados (HAYMAN, 1982;LAMBERT et al, 1980). O uso de inóculo misto, composto por espécies com diferentes estratégias, pode apresentar resultados melhores para plantas hospedeiras e pode, conseqüentemente, ser mais adequado do que a introdução de uma única espécie de fungo (DAFT, 1983 O substrato utilizado no experimento foi proveniente de uma amostra de solo classificado como Neossolo Quartzarênico (EMBRAPA, 2006) misturado com uma parte de areia de rio lavada (2:1).…”
Section: Introductionunclassified
“…In addition to this monosporic inoculant, it is possible to produce inoculant with different native species with greater ease and speed (Lambert et al, 1980;Hayman, 1982). In comparison with the commercial inoculant, it has a low cost, higher taxonomic diversity, and the use of locally adapted species (Schwartz et al, 2006;Douds Jr. et al, 2010), which increases the chances of positive effects on the plant (Klironomos, 2003) and avoid the introduction of exotic species (Ijdo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%